Seismic performance of trusses under earthquake loadings - Nor Ares, Yahya (2019)
The study was conducted because there might be a tremors in Malaysia because we are at active tectonic plate and also there will be seismic wave generated from the earthquake that occurred in neighbouring countries. Therefore, engineers are concerned about the seismic vulnerability of trusses structures due to lack of earthquake consideration in Malaysia's building design procedure. Trusses structure is the critical structure that will damage cause by the seismic effect and also important component in building system. With this, trusses is modelled and analysed using Finite Element Modelling (FEM) by SAP2000 software under various type of analysis that cover Free Vibration Analysis (FVA), Time History Analysis (THA) and Respond Spectrum Analysis (RSA) under the different earthquake loading. The earthquake loading data is taking from Acheh and El-Centro earthquake that had been record by Malaysia Meteorological Department. Implementation between two types of different earthquake loading will represent the contrasting of dynamic characteristic of trusses structure. Furthermore, the overall seismic performance of trusses significantly enhanced in longitudinal and transverse directions. It can summarize that the design of the trusses is stable and ability to withstand under major and minor earthquake and also can yield adequate resistance against different earthquake loading.